ASPEK KOGNITIF DAN AFEKTIF MASYARAKAT TERHADAP MANAJEMEN PELAYANAN KIA DI KABUPATEN JEMBER - Eri Witcahyo (Jurnal Ilmu Kesehatan Masyarakat, 2015)
Jember is one of the districts with high MMR (102/100.000 live births) and IMR (23/1000 live births) at 2015 in East Java. This indicates that the service utilization Antenatal Care (ANC) in the existing health care facilities in Jember still not optimal. Most of the causes of health care utilization that occurred in the community affected by the behavior of the model of society in choosing and utilizing the health service. Identify the distribution of respondents' knowledge and attitudes about the MCH services. The study is a descriptive observational study with cross sectional design. The unit of analysis of this study is the entire women who have earned MCH services, with a sample of 29 respondents. Respondents assess the health services provided are good (96.6%), whereas the components of MCH services, materials and medicine, counseling, care of infants and toddlers and the availability of staff each got a good assessment of 96.6%, laboratory services and physical facilities laboratory respectively 65.5% and 69%. In the knowledge about the treatment of infants, children and infants, respondents is low include the treatment itself against infant diarrhea (69%) and supplementary feeding after 6 months (72.4%).Keywords: cognitive, affective, management, MCH services